2012
DOI: 10.1530/joe-12-0108
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine cathepsin S processes leptin, inactivating its biological activity

Abstract: Leptin is a 16 kDa hormone mainly produced by adipocytes that plays an important role in many biological events including the regulation of appetite and energy balance, atherosclerosis, osteogenesis, angiogenesis, the immune response, and inflammation. The search for proteolytic enzymes capable of processing leptin prompted us to investigate the action of cysteine cathepsins on human leptin degradation. In this study, we observed high cysteine peptidase expression and hydrolytic activity in white adipose tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…There are specific details to highlight regarding the differences among cathepsins K, L, and S. CatS appeared to degrade the fibrin gel faster than the other proteases in this in vitro study, but it may not necessarily be a better fibrinolytic enzyme than plasmin in vivo ; there are pH dependent and environmental cofactors that must be considered, but this deserves further investigation since catS is unique among cysteine cathepsins in that it retains its activity at neutral pH [10, 34]. Additionally, cathepsin S was shown to be elevated in the plasma of patients with diabetes [35, 36], associated with wound healing and hemostatic abnormalities, and other cardiovascular diseases, which may be a biomarker for these diseases [29, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…There are specific details to highlight regarding the differences among cathepsins K, L, and S. CatS appeared to degrade the fibrin gel faster than the other proteases in this in vitro study, but it may not necessarily be a better fibrinolytic enzyme than plasmin in vivo ; there are pH dependent and environmental cofactors that must be considered, but this deserves further investigation since catS is unique among cysteine cathepsins in that it retains its activity at neutral pH [10, 34]. Additionally, cathepsin S was shown to be elevated in the plasma of patients with diabetes [35, 36], associated with wound healing and hemostatic abnormalities, and other cardiovascular diseases, which may be a biomarker for these diseases [29, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulatory roles in adipogenesis have also been described for cathepsin S and its expression levels were found to be significantly influenced by metabolic changes (see Taleb and Clement , 2007 for a review). Cathepsins K and S, but not L, were also found to degrade leptin in vitro , but only cathepsin S was able to do so at pH 7.4 (Oliveira et al , 2012 ).…”
Section: Cathepsin K In Adipogenesis and Obesitymentioning
confidence: 93%
“…Recent research has also identified a plethora of extracellular substrates for cathepsin S, including the basement membrane component nidogen-1 (115) , the epithelial sodium channel (116) , leptin (117) , and plasminogen (118) . Similar to cathepsins B and X, cathepsin S has also been found associated with the cell surface (119) .…”
Section: Cathepsin L-like Peptidasesmentioning
confidence: 99%